Plasma Levels of Free and Total TFPI, Relationship with Cardiovascular Risk Factors and Endothelial Cell Markers - Morange, P. E.; Renucci, J. F.; Charles, M. A.; Aillaud, M. F.; Giraud, F.; Grimaux, M.; Juhan-Vague, I. (Thrombosis and Haemostasis, 2001)
Free-TFPI (f-TFPI) presents high anticoagulant activity and its plasma level correlates with unfavorable outcomes in unstable angina. Total TFPI (t-TFPI) represents mainly the lipid-bound form which seems to have a poor anticoagulant activity. Until now, it is not known whether the variations of f-TFPI plasma levels are determined by environmental factors. The aim of our study was to evaluate the influence of cardiovascular risk factors on plasma levels of f-TFPI and relations with other endothelial derived molecules in a population of 626 patients (277 men and 349 women) attending a metabolic ward for primary prevention of coronary disease.Free and total TFPI plasma levels were poorly correlated. f-TFPI levels increased with age in both sexes, t-TFPI in women only. Ageadjusted correlations of TFPI levels with conventional cardiovascular risk factors and endothelial cell markers showed different patterns for f-TFPI and t-TFPI. f-TFPI correlated with parameters associated with insulin resistance, particularly in females. f-TFPI was also positively associated in both genders with fibrinogen and endothelial cell markers: t-PA, thrombomodulin (TM) and von Willebrand factor (vWF). t-TFPI correlated strongly with LDL-C in both sexes. It also correlated negatively with parameters of the insulin resistance syndrome. t-TFPI also correlated with TM but not with other endothelial cell markers. The results of the multivariate step by step analysis showed that cardiovascular risk factors poorly explained the f-TFPI variability (7% and 4% in men and women, respectively), whereas they explained 16 and 20% of t-TFPI variability in men and women respectively (mostly related to LDL-C).In conclusion, this study showed that free- and total-TFPI are regulated differently. f-TFPI strongly correlates with endothelial cell markers and t-TFPI is more related to conventional cardiovascular risk factors. The strong gender effect on f-TFPI levels remains to be explained.
Keywords: Free/total TFPI; cardiovascular risk factors; endothelial cell markers